2006
DOI: 10.1111/j.1468-3083.2006.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous mycosis produced by Aureobasidium pullulans in a renal transplant recipient

Abstract: 229 2 Fernandes JC, Correia TM, Azevedo F, Mesquita-Guimaraes J. Tufted hair folliculitis after scalp injury. Cutis 2001; 67: 243-245. 3 Smith NP, Sandersn KV. Tufted folliculits of the scalp. J R Soc Med 1978: 606-608. 4 Pujol RM, Garcia-Patos V, Ravella-Mateu A, Casanova JM, de Moragas JM. Tufted hair folliculitis: a specific disease? Br J Dermatol 1994; 130: 259-260. 5 Powell JJ, Dawber RP, Gatter K. Folliculitis decalvans including tufted folliculitis: clinical, histological and therapeutic findings. Br J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Arranz Sánchez et al reported similar [18] skin lesions in a renal transplant recipient caused by A. pullulans which subsided within 2 months of ITR therapy with no relapse at one year of follow-up. However in our case the lesions recurred after 2 months despite the patient being on antifungal agents.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Arranz Sánchez et al reported similar [18] skin lesions in a renal transplant recipient caused by A. pullulans which subsided within 2 months of ITR therapy with no relapse at one year of follow-up. However in our case the lesions recurred after 2 months despite the patient being on antifungal agents.…”
Section: Discussionmentioning
confidence: 95%
“…However in our case the lesions recurred after 2 months despite the patient being on antifungal agents. How long these lesions have to be treated has not been clearly defined [18, 19]. This case also highlights how crucial it is to optimize the TAC dose and monitor for nephrotoxicity when the patient is treated with antifungal drugs such as triazoles, owing to the drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Culture and microscopic examination remain the definitive methods to identify these fungi. Skin infections can be seen in immunocompetent hosts with soil‐contaminated wounds or with the introduction of foreign bodies into the skin, but it is now known to have been documented as causing cutaneous infection to invasive and potentially life‐threatening infections in humans . Among immunocompromised patients, organ transplant recipients may be at particularly higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated systemic infections by A. pullulans are very rare and occur in patients on broad‐spectrum antibiotics, invasive devices such as central venous catheters, and in immunocompromised patients . In an extensive search of the literature, we could find only three pediatric patients with A. pullulans fungemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation